Expression of TLR4 and its effect on Treg cells in early pregnancy decidual stromal cells after lipopolysaccharide treating. (June 2019) - Wu, Ali; Liu, Fumin; Liu, Xiaoyun; Feng, Xia; Lin, Hua
Abstract: Objective: To investigate the expression of TLR4 in human early pregnancy decidual stromal cells (DSCs) induced by lipopolysaccharide (LPS) and its effect on the peripheral blood regulatory T (Treg) cells subgroup in women of childbearing age. Method: Isolating and cultivating normal human early pregnancy DSCs followed by treatment with 0, 25, 50, 100 and 200 ng/ml LPS, and the expression level of TLR4 mRNA was detected by RT-PCR. After 3 or 4 generation we divide the DSCs into 5 groups: ①Control group: Cultivation of peripheral blood lymphocyte (PBLC); ②Co-cultivation group: Co-cultivation of PBLC and DSCs; ③LPS stimulation group: PBLC + DSCs + LPS; ④PDTC blocking-up group: PBLC + DSCs + LPS + PDTC; ⑤TLR4 blocking-up group: PBLC + DSCs + LPS + TLR4mAb. In ①–④ groups, western blot was used to detect the expression of inhibitory factor-κB (IκB-α) protein and RT-PCR was used to detect the expression of FoxP3 mRNA. In ①–⑤ groups, flow cytometry was applied to detect the percentage of Treg cells subgroup. Results: The purity of primary cultured DSCs was more than 95%. RT-PCR results showed that the expression level of TLR4 mRNA increased gradually with the augment of LPS concentration. Western blot and RT-PCR showed that the expression of IκBα protein and FoxP3 mRNA in the other 3 groups was significantly higher than that in the control group ( P  <  0.05), and the expression of IκBα protein and FoxP3 mRNA in LPS stimulation group was lower than that in the co-cultivation group ( P  <  0.05). Compared with the LPS stimulation group, the expression of IκBα protein and FoxP3 mRNA in PDTC blocking-up group was higher than that in the LPS stimulation group ( P  <  0.05), but still lower than the co-cultivation group ( P  <  0.05). The proportion of Treg cells in the other 4 groups detected by flow cytometry was significantly higher than that in the control group ( P  <  0.05). Compared with the co-cultivation group, the Treg cells ratio of the LPS stimulation group was significantly decreased ( P  <  0.05). The proportions of Treg cells in PDTC blocking-up group and TLR4 blocking-up group were higher than that in the LPS stimulation group, but still lower than that in the co-cultivation group ( P  <  0.05). There was no significant difference between the PDTC blocking-up group and the TLR4 blocking-up group ( P > 0.05). Conclusion: Human early pregnancy DSCs can promote the differentiation of Treg cells. LPS can stimulate the expression of TLR4 in early pregnancy DSCs and decrease the proportion of Treg cells in PBLC, with NF-κB signaling pathway being the potential underlying mechanisms.